2016 World Health Organization Classification of Central Nervous System Tumors. Issue 6 (December 2017) - Wen, Patrick Y.; Huse, Jason T.
Abstract : ABSTRACT: Purpose of Review: Since 1979, the World Health Organization (WHO) has periodically published a consensus classification and grading of tumors of the central nervous system (CNS) to ensure uniform histopathologic diagnostic criteria worldwide. In 2016, the WHO published an update of the fourth edition of the classification of CNS tumors. This article summarizes the major changes in the update and discusses their impact on clinical practice. Recent Findings: For the first time, the 2016 revision of the WHO classification uses molecular parameters in addition to traditional histology to diagnose many CNS tumors, resulting in major restructuring of the classification of many tumors, especially gliomas, ependymomas, and medulloblastomas. Accordingly, nomenclature for selected entities now includes both a histopathologic diagnosis and defining molecular features. Summary: The use of integrated phenotypic and genotypic parameters for the classification of CNS tumors introduces greater objectivity to the diagnosis but also requires more widespread availability of molecular testing. It is hoped that these changes will lead to greater diagnostic accuracy with more biologically homogeneous diagnostic entities and improved patient management and determination of prognosis.